STUDY OF DEFORMABILITY OF THE LARGE-SPAN ROOF STRUCTURAL SYSTEM IN THE FORM OF AN ASYMMETRICAL SHELL - Naboka, A.; Firsov, P. (Municipal economy of cities. Series: «Economy science», 2024)
The scientific article is devoted to a complex study of deformability of saddle-type shell of negative Gaussian curvature of a public object that has been in operation for a long time for further general restoration of the building’s roofing system. The authors have developed a specific algorithm for conducting experimental research, providing additional static load on a shell at the lower point of the gentle axial line of the supporting arches. To smoothly carry out the loading procedure, we mounted containers in barrel form on the roof surface and gradually filled them with water. We carried out an experimental evaluation of the bearing capacity of the shell with the determination of the redistribution of forces along the length of the section in the lower zone of the conventionally outlined arch. The experimental test results revealed that the deformability of the shell surface under short-term loading did not exceed 2.0 mm, and, under long-term loading, it was no more than 4.0 mm. Analysis of the qualitative features of structure deformation shows that the displacement of the roof’s points, located symmetrically to the vertical axis, has the opposite sign to the sign of the displacement of the actual ‘saddle’ point (the case of symmetrical deformation). We conducted a numerical verification of the behaviour of the investigated structure by forming a detailed finite element spatial model of the shell. Comparison of the results of numerical calculation with the results of field tests shows the coincidence of qualitative and quantitative parameters, which, in turn, characterises the developed theoretical model as fully adequate and suitable for analysing the stress-strain state of similar large-span structural systems. Based on the results of comprehensive theoretical and experimental research, we made proposals for the further restoration of the roofing structure with the limitation of the self-weight of the covering to 1 kN/m2. Engineers and scientists can use the research results to reconstruct similar authentic structural systems.